Three types of ligamentum flavum resections for the treatment of lumbar central canal stenosis: BUTTERFLY retrospective study - Ariel Kaen; Santiago Rocha Romero; María Jesús Correa Romero; Fernando Durand; Ignacio Martin (Asian Spine Journal)
Study Design Retrospective analysis of a prospective study. Purpose The study aimed to evaluate and compare the clinical results of three surgical techniques for the resection of the hypertrophic ligamentum flavum in patients with lumbar stenosis. Overview of Literature Lumbar spinal stenosis is a common degenerative condition. Biportal endoscopic surgery is a modern technique that has gained popularity in recent years. Although various techniques have been proposed for resecting the ligament, no studies have identified the most superior method. Methods This retrospective study enrolled patients with severe lumbar canal stenosis who underwent biportal endoscopic “Z” technique decompression between 2021 and 2023. Patients with any clinical or radiological signs of spondylolisthesis were excluded. The resection of the ligamentum flavum was classified into piecemeal resection, one-piece “butterfly” resection, and the novel variant “two-wings” or two-piece resection. Several demographic and clinical statistical variables were collected, with a specific focus on surgical time, postoperative complications, and clinical outcomes. Results Ninety lumbar decompression surgeries were performed on 70 patients. The patients were divided into the butterfly group (en bloc) with 27 levels, “two-wings” group with 35 levels, and “piecemeal” group with 28 levels. No significant differences in demographics or clinical variables were found among the three groups. However, piecemeal resection was associated with a higher incidence of dural tears and a longer surgical time (p<0.05). In contrast, en bloc resection, particularly in the two-wing group, demonstrated the best surgical times without an increase in complication rates. Conclusions The results revealed that removing the ligamentum flavum en bloc (either in two pieces or one) may reduce the surgical time and incidence of dural tears. Randomized and prospective studies are warranted to establish definitive conclusions.